The Heterogeneity, Origins, and Impact of Migratory iILC2 Cells in Anti-helminth Immunity - Miller, Mindy M.; Reinhardt, R. Lee (Frontiers in Immunology, 2020)
Soil-transmitted helminths represent a major global health burden with infections and infection-related comorbidities causing significant reductions in the quality of life for individuals living in endemic areas. Repeated infections and chronic colonization by these large extracellular worms in mammals led to the evolution of type-2 immunity characterized by the production of the type-2 cytokines interleukin (IL)-4, IL-5, and IL-13. Although a number of adaptive and innate immune cells produce type-2 cytokines, a key cellular source in the context of helminth infection is group 2 innate lymphoid cells (ILC2s). ILC2s promote mucosal barrier homeostasis, integrity, and repair by rapidly responding to epithelial cues in mucosal tissues. Though tissue-resident ILC2s (nILC2s) have been studied in detail over the last decade, considerably less is known with regard to a subset of inflammatory ILC2s (iILC2s) that migrate to the lungs of mice early after Nippostrongylus brasiliensis infection and are potent early producers of type-2 cytokines. This review will discuss the relationship and differences between nILC2s and iILC2s that establish their unique roles in anti-helminth immunity. We have placed particular emphasis on studies investigating iILC2 origin, function, and their potential long-term contribution to tissue-resident ILC2 reservoirs in settings of helminth infection.